TOPICAL ISSUES OF THE CONTENT OF LEGAL CULTURE - Akhmetov Арман; Zhamuldinov Виктор (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2022)
The presented article provides a systematic analysis of the nature of legal culture and its influence on the lawful behavior of an individual, as well as the degree of his trust in the legal system and law enforcement agencies. The aim of the work is to reflect the content and essence of legal culture, its significance in the formation of the legal consciousness of the individual and society as a whole. When writing the article, general scientific research methods were used, including the logical method, synthesis, analysis and survey results. The study of legal culture shows the diversity of its forms of implementation and effectiveness in the fight against corruption and legal nihilism. The article shows that the formation of a high level of legal culture becomes possible through the instillation of a lawful model of behavior in the population, the growth of the identification of law in the public mind and the legal literacy of every citizen. The issues of development of legal culture and legal consciousness directly depend on the effectiveness of interaction with various institutions of civil society, which act as real indicators of legal consciousness, both for an individual and for society as a whole. The scope of the results of the work is reduced to the fact that the materials of the article can be used both in the educational process and in the creation of regulatory documents, state programs and concepts on anti-corruption policy and the development of legal culture. At the end of the article, it was concluded that the level of legal culture determines the success and quality of the ongoing legal policy in the state, recommendations and proposals are also given aimed at creating positive practices in the direction of the evolution of the entire legal system, combating legal nihilism and corruption in society. Key words: law, legal culture, legal consciousness, state, society, personality, education, system, legal model, corruption, legal nihilism.